Comparison of blood pressure in deaf secondary school children and their hearing counterparts: association between noise and blood pressure (2006)
Background and Objective: High blood pressure has been known to be one of the problems that could develop as a result of exposure to noise. Consequently, those who are hearing impaired are thought to be immune to this. This study assessed the relationship between noise exposure and blood pressure. Methodology: This is a comparative prospective study involving participants (consisting of the hearing and the hearing impaired) drawn from a school environment that is situated close to a major highway and railway and evaluating the impact of noise on their blood pressure. Results: The study population consisted of 299 secondary school students. The noise sensitive group comprised 220 participants with normal hearing while the noise-insensitive group comprised 79 hearing impaired from the same school. More participants 6 (85.7%) from the noise insensitive group were found to have significantly higher blood pressure than their hearing counterparts 1 (14.3%). In addition, majority of the participants (63.1 %) irrespective of their level of noise sensitivity were underweight. Conclusion: This study finds liaise exposure alone not sufficient to bring about an increase in blood pressure of the studied population. This not withstanding we advocate for policy measures aimed at controlling the source of environmental noise around educational institution which will aid in reducing the adverse effects of noise on the school children.